Business Legality Assistance for Small and Medium Enterprise as An Effort to Protect the Law in the Context of Post-Pandemic Economic Recovery - Hanin Alya' Labibah; Achmad Ryan Nur Sahrudin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Business legality is a standard that must be met by stakeholders and an effort to validate their business. Business legality is a form of authorization and issuance of business activity licenses carried out by business owners or companies of authorized parties. So the legitimacy of the business is one that must be fulfilled by business owners to legalize their business legally. However, business legitimacy is often overlooked by business actors including micro, small and medium enterprises (MSMEs). The purpose of this assistance is to provide education to the community, especially to the owners of MSMEs kafa Berkah in Sumbangtimun Village, Trucuk District, Bojonegoro Regency. Business legality documents serve to protect MSMEs in the eyes of the law. The method of service implementation takes place through socialization to the village government, community leaders, small business owners in Sumbangtimun Village. The results obtained in this activity are awareness of human resources and resources related to the importance of business legality making guidelines for managing legality documents for small and medium enterprises.